Influence of the lateral pterygoid muscle on traumatic temporomandibular joint bony ankylosis. Issue 1 (December 2016) - Deng, Tian-ge; Liu, Chang-kui; Liu, Ping; Zhang, Lin-lin; Wu, Li-geng; Zhou, Hong-zhi; Ding, Yu-xiang; Hu, Kai-jin
Abstract Background The pathogenesis of traumatic TMJ ankylosis remains unclear. This study aimed to verify the role of the lateral pterygoid muscle in the pathogenesis of traumatic temporomandibular joint (TMJ) bony ankylosis. Methods Eight 6-month-old male sheep were used in this study. Bilateral TMJ osteotomies were performed to induce sagittal fractures of the mandibular condyle. The lateral one-fourth segment of the disc was removed to establish a model of TMJ bony ankylosis. Subsequently, the function of the left and right lateral pterygoid muscles was blocked (experimental group) or maintained (control group), respectively. At 12 weeks postoperatively, animals were sacrificed and TMJ complex samples were evaluated by gross observation, spiral computed tomography (CT), micro-CT, and histological examinations. Results Gross observation revealed bony ankylosis in the control TMJs and fibrous adhesions in the experimental TMJs. Spiral CT and micro-CT demonstrated that, compared to the experimental group, the control group showed calcified callus formation in the joint space and roughened articular surfaces after new bone formation, which protruded into the joint space. Maximum mediolateral and anteroposterior condylar diameters were significantly larger in the control group than in the experimental group. Micro-CT also showed that the primary growth orientation of new trabeculae was consistent with the direction of lateral pterygoid traction in the control group, but not in the experimental group. Histological examination showed fibro-osseous ankylosis in the control group, but not in the experimental group. Conclusions The lateral pterygoid simulates the effects of distraction osteogenesis, which is an important factor in the pathogenesis of TMJ bony ankylosis during the healing of sagittal condylar fractures.